Globalising Democracy : Party Politics in Emerging Democracies. - Burnell, Peter. (Routledge Studies in Globalisation Series, 2006)
This new volume brings together expert contributors to explore the intersection of two major contemporary themes: globalization, and the contribution that both domestic party politics and international party support make to democratization.